A systematized approach to obtain dependable controllers specifications - Machado, José Mendes (2010)
This paper is focused on the problem that a designer, of an automation system controller, must solve that is related with the correct synchronization between different parts of the controller specification when this specification obeys at a previous defined structure. If this synchronization is not done according some rules, and taking some aspects in consideration, some dependability aspects, concerning the desired behavior for the system, may not be accomplished. More specifically, it is shown, in the paper, a systematized approach that consists in using the GEMMA and the SFC formalisms for the structure and specification of all the system behavior, considering all the stop states and functioning modes of the system. The synchronization of the models, corresponding of the controller functioning modes and of the controller stop states, is shown in detail and it is presented a systematized approach for this synchronization. For this, there are discussed, on the paper, the advantages and disadvantages of the Vertical coordination and Horizontal coordination proposed by the GEMMA formalism. A case study is presented to explain the proposed systematic approach. A complete safe controller specification is developed to control a hybrid plant.